Climate Ambition and Sustainable Development for a New Decade: A Catalytic Framework. Issue 3 (6th April 2021) - Chan, Sander; Boran, Idil; van Asselt, Harro; Ellinger, Paula; Garcia, Miriam; Hale, Thomas; Hermwille, Lukas; Liti Mbeva, Kennedy; Mert, Ayşem; Roger, Charles B.; Weinfurter, Amy; Widerberg, Oscar; et al.
Abstract: This paper examines the Global Climate Action Agenda (GCAA) and discusses options to improve sub‐ and non‐state involvement in post‐2020 climate governance. A framework that stimulates sub‐ and non‐state action is a necessary complement to national governmental action, as the latter falls short of achieving low‐carbon and climate‐resilient development as envisaged in the Paris Agreement. Applying design principles for an ideal‐type orchestration framework, we review literature and gather expert judgements to assess whether the GCAA has been collaborative, comprehensive, evaluative and catalytic. Results show that there has been greater coordination among orchestrators, for instance in the organization of events. However, mobilization efforts remain event‐driven and too little effort is invested in understanding the progress of sub‐ and non‐state action. Data collection has improved, although more sophisticated indicators are needed to evaluate climate and sustainable development impacts. Finally, the GCAA has recorded more action, but relatively little by actors in developing countries. As the world seeks to recover from the COVID‐19 crisis and enters a new decade of climate action, the GCAA could make a vital contribution in challenging times by helping governments keep and enhance climate commitments; strengthening capacity for sub‐ and non‐state action; enabling accountability; and realizing sustainable development. Abstract : While the extent to which the pre‐2020 agenda was able to generate new and additional action is difficult to determine, by highlighting expanding engagement, the GCAA helped to drive relative optimism and the momentum for climate action, even when the climate regime was confronted with severe setbacks.